Impact of epicardial adipose tissue increase after ST elevation Myocardial Infarction (STEMI) on IL-13 and left ventricular remodelling. (25th November 2020) - Parisi, V; Cabaro, S; D'Esposito, V; Petraglia, L; Conte, M; Gerundo, G; Campana, P; Caruso, A; Grimaldi, M.G; Pilato, E; Comentale, G; Leosco, D
Abstract: Background: The role of epicardial adipose tissue (EAT) in myocardial diseases is well established, and several evidence suggest that EAT may negatively affect left ventricular (LV) remodelling through an imbalanced production and secretion of pro and anti-inflammatory cytokines. Of these, the IL-13 it is known to play a positive activity on cardiac remodelling. Nowadays, the crosstalk between EAT and the myocardium is still poorly understood and the effects of myocardial ischemia on morphological and functional properties of EAT are almost unknown. Purpose: In the present study we explored whether an increase of EAT thickness after STEMI might be associated with unfavourable LV remodelling at 3 months (T1). We also evaluated the relationship between changes (Δ) of EAT thickness and systemic levels of Interleukin (IL)-13 which is known to play a favourable activity on LV remodelling after STEMI. Methods: We enrolled 66 patients with first STEMI, undergoing primary percutaneous angioplasty. At baseline and at 3 months we performed a complete echocardiogram, including EAT maximal thickness assessment, and determined circulating levels of IL-13. Results: At 3 months after STEMI, the population was stratified into two groups according to different EAT remodelling after cardiac event: Group 1, patients with an increased EAT thickness (Δ EAT>1; 30 patients) and Group 2, patients with unchanged or decreased EAT thickness (Δ EAT<1). The two groups did not differ for age, gender and atherosclerotic risk factors. Group 1 had a worse LV remodelling at 3 months with higher LV diastolic and systolic volumes, lower LV ejection fraction (p=0.003; p=0.013; p=0.013 respectively) and worse diastolic function (E/e'; p=0.011). Of interest, EAT thickness increase was paralleled by circulating IL-13 reduction (p=0.022). Conclusion: Myocardial injury can result in EAT increase which is associated to worse LV remodelling probably through the loss of the protective role of IL-13. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This research has been funded by the University of Naples "Federico II" and "Compagnia di San Paolo e l'Istituto Banco di Napoli" within the competitive grant STAR 2018; Valentina Parisi is the principal investigator